2019
DOI: 10.24095/hpcdp.39.5.03
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review on the relations between urban form and health: a focus on Canadian quantitative evidence

Abstract: Introduction Despite the accumulating Canadian evidence regarding the relations between urban form and health behaviours, less is known about the associations between urban form and health conditions. Our study aim was to undertake a scoping review to synthesize evidence from quantitative studies that have investigated the relationship between built environment and chronic health conditions, self-reported health and qual¬ity of life, and injuries in the Canadian adult population. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 94 publications
(102 reference statements)
2
32
1
Order By: Relevance
“…It is well established that physical activity in and of itself can reduce symptoms of depression [ 10 , 11 ], improve anxiety [ 12 ], and increase quality of life [ 13 ]. In several recent reviews, the availability of useable greenspace and proximity to parks were significantly associated with multiple health outcomes among urban residents, including lower weight status, reduced cardiovascular disease and diabetes risk, lower levels of anxiety and depression, reduced stress, and better quality of life [ 14 , 15 , 16 , 17 , 18 ]. Being outdoors in green spaces, away from work, and with family and friends may even provide immediate boosts in self-reported happiness, as demonstrated in a large sample of London, UK residents [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that physical activity in and of itself can reduce symptoms of depression [ 10 , 11 ], improve anxiety [ 12 ], and increase quality of life [ 13 ]. In several recent reviews, the availability of useable greenspace and proximity to parks were significantly associated with multiple health outcomes among urban residents, including lower weight status, reduced cardiovascular disease and diabetes risk, lower levels of anxiety and depression, reduced stress, and better quality of life [ 14 , 15 , 16 , 17 , 18 ]. Being outdoors in green spaces, away from work, and with family and friends may even provide immediate boosts in self-reported happiness, as demonstrated in a large sample of London, UK residents [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The literature is characterized by measurement inconsistency, a lack of longitudinal and intervention studies and little geographic variability, with a scarcity of studies on rural and Indigenous communities. Another scoping review 12 on urban form and health in Canada found that most studies that examined food environment access measures and health outcomes such as weight status, cardiovascular disease and diabetes reported at least one statistically significant association.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence demonstrating associations between the neighborhood environment and chronic disease [26,27], well-being [28], and physical activity [29,30] exists, yet few studies have investigated the relations between the neighborhood built environment and fitness [31][32][33][34][35]. For example, Hoehner et al [31] found positive associations between objectively-measured neighborhood intersection density, vegetation coverage, and count of private exercise facilities and objectively-measured CRF.…”
Section: Introductionmentioning
confidence: 99%